Controlled (Co)Polymerization of Methacrylates Using a Novel Symmetrical Trithiocarbonate RAFT Agent Bearing Diphenylmethyl Groups - Alvaro Leonel Robles Grana; Hortensia Maldonado-Textle; José Román Torres-Lubián; Claude St Thomas; Ramón Díaz de León; José Luis Olivares-Romero; Luis Valencia; Francisco Javier Enríquez-Medrano (Molecules, 2021)
Herein, we report a novel type of symmetrical trithiocarbonate chain transfer agent (CTA) based diphenylmethyl as R groups. The utilization of this CTA in the Reversible Addition-Fragmentation chain Transfer (RAFT) process reveals an efficient control in the polymerization of methacrylic monomers and the preparation of block copolymers. The latter are obtained by the (co)polymerization of styrene or butyl acrylate using a functionalized macro-CTA polymethyl methacrylate (PMMA) previously synthesized. Data show low molecular weight dispersity values (Đ < 1.5) particularly in the polymerization of methacrylic monomers. Considering a typical RAFT mechanism, the leaving groups (R) from the fragmentation of CTA should be able to re-initiate the polymerization (formation of growth chains) allowing an efficient control of the process. Nevertheless, in the case of the polymerization of MMA in the presence of this symmetrical CTA, the polymerization process displays an atypical behavior that requires high [initiator]/[CTA] molar ratios for accessing predictable molecular weights without affecting the Đ. Some evidence suggests that this does not completely behave as a common RAFT agent as it is not completely consumed during the polymerization reaction, and it needs atypical high molar ratios [initiator]/[CTA] to be closer to the predicted molecular weight without affecting the Đ. This work demonstrates that MMA and other methacrylic monomers can be polymerized in a controlled way, and with “living” characteristics, using certain symmetrical trithiocarbonates.